Functional Assay of Cancer Cell Invasion Potential Based on Mechanotransduction of Focused Ultrasound - Weitz, Andrew C.; Lee, Nan Sook; Yoon, Chi Woo; Bonyad, Adrineh; Goo, Kyo Suk; Kim, Seaok; Moon, Sunho; Jung, Hayong; Zhou, Qifa; Chow, Robert H.; Shung, K. Kirk (Frontiers in Oncology, 2017)
Cancer cells undergo a number of biophysical changes as they transform from an indolent to an aggressive state. These changes, which include altered mechanical and electrical properties, can reveal important diagnostic information about disease status. Here we introduce a high-throughput, functional technique for assessing cancer cell invasion potential, which works by probing for the mechanically excitable phenotype exhibited by invasive cancer cells. Cells are labeled with fluorescent calcium dye and imaged during stimulation with low-intensity focused ultrasound, a non-contact mechanical stimulus. We show that cells located at the focus of the stimulus exhibit calcium elevation for invasive prostate (PC-3 and DU-145) and bladder (T24/83) cancer cell lines, but not for noninvasive cell lines (BPH-1, PNT1A, and RT112/84). In invasive cells, ultrasound stimulation initiates a calcium wave that propagates from the cells at the transducer focus to other cells, over distances greater than 1 mm. We demonstrate that this wave is mediated by extracellular signaling molecules and can be abolished through inhibition of transient receptor potential channels and inositol trisphosphate receptors, implicating these proteins in the mechanotransduction process. If validated clinically, our technology could provide a means to assess tumor invasion potential in cytology specimens, which is not currently possible. It may therefore have applications in diseases such as bladder cancer, where cytologic diagnosis of tumor invasion could improve clinical decision-making.